Preparation and Study of the Optical Properties of Poly (3-hexylthiophene-Co-thiophene) @NPs (SiO2 , ZnO , Ag) - Ahmed Ismael; Hussein F.Hussein; Salah S. Al-luaibi (European Science Publishing, 2024)
The study explores enhancing the optical of hybrid polymers by incorporating Poly(3HT-co-Thio)@NP (SiO2, ZnO, Ag ) into photo-electro-active layers useful in solar cell applications. These materials were examined and analysed using various techniques like X-ray diffraction (XRD), scanning electron microscopy (SEM), Fourier transform infrared spectroscopy (FTIR), Atomic Force Microscopy (AFM), and UV-visible Absorption Spectrum. XRD analysis revealed high crystallinity in Poly(3HT-co-Thio)@SiO2, ZnO and Ag, with crystallite sizes between 70–80 nm. UV-visible absorption tests indicated band gap values of 1.78 eV, 1.82 eV, and 1.75 eV for SiO2, ZnO and Ag respectively the synthesized nanoparticles. The polymeric membrane exhibited varying thicknesses of approximately 10.2 nm, 15.4 nm, and 155 nm, with surface roughness values of 5.19 nm, 6.48 nm, and 73.9 nm for SiO2, ZnO and Ag respectively of the polymer films. Analysis revealed a range of less than 100 nm for Poly(3HT-co-Thio)@SiO2 and ZnO, measuring 63.3 nm due to agglomeration. Additionally, the polymer film on the nanoparticles varied in thickness from 5nm to 19 nm, indicating a thin, transparent layer capable of efficiently transmitting light.
Keywords: Poly(3HT-co-Thio)@NPs (SiO2,ZnO,Ag),Optical properties ,Nano particles.